FALSE POSITIVE HIV TEST IN LOW PREVALENCE REGION: PAKISTAN - Ikram, Nadeem; Ahmad, Sajid (Journal of Ayub Medical College Abbottabad, 2012)
The prevalence of HIV in Pakistan is less than 0.1%, but is feared to be spreading among the general population rapidly. Screening tests for HIV is based on antibody detection. There seems to be little knowledge regarding the interpretation of HIV results among the population. Most often the patients are being issued a positive HIV report based on single screening test when in fact it should be confirmed before issuing a positive HIV result. There is a lot of stigma associated with the disease in Pakistan, on the other hand the test is done mostly without counselling services hence causing physical and mental trauma to the patients. Keywords: HIV, false positive, Pakistan, AIDS, ELISA